"I Hate Group Work!": Addressing Students' Concerns About Small-Group Learning - Elizabeth G. Allan, PhD (Park University, 2017)
This article identifies the strategies used by architecture professors and their undergraduate students to mitigate common issues that students raise about group work. Based on participant-observation, interviews with students and faculty, and analysis of instructional materials and student work, this IRB-approved ethnographic case study complicates the separation of collaborative, cooperative, and problem-based learning into distinct pedagogical models. Rather than viewing students' concerns as a form of resistance that can be avoided with the right approach to small-group learning, this article explores how the hybrid model operating in design studio pedagogy confronts the problems inherent in any form of group work.